How to calculate $ \lim_{x\to 0} (\frac{(5x + 1)^{20} – (20x + 1)^{5}}{\sqrt[5]{1 + 20x^{2}}-1}) $ without the rule of L’Hôpital?

$ $ \lim_{x\to 0} (\frac{(5x + 1)^{20} – (20x + 1)^{5}}{\sqrt[5]{1 + 20x^{2}}-1}) $ $

Hello! I need to solve this limit. I had solved it with the rule of L’Hôpital, but i can’t without it. I tried multiplicatio using Special Limits, but i simplified it only to $ $ \lim_{x\to 0} (\frac{e^{100x} – e^{100x}}{e^{4x^2}-1})$ $ Please help me, I must solve it using only Special Limits and simple transformations. I can’t use derivatives.